Dynamics and power flow behaviour of a nonlinear vibration isolation system with a negative stiffness mechanism - Yang, J.; Xiong, Y.P.; Xing, J.T. (Journal of sound and vibration, 2013)
The dynamics and power flow behaviour of a nonlinear vibration isolation system with a negative stiffness mechanism (NSM) are studied. The mathematical equations governing the nonlinear dynamics of the system are derived. The averaging method is used to obtain the frequency response function of the system subject to harmonic excitations. It is found that adding NSM can greatly enlarge the frequency band for effective vibration isolation. Numerical simulations reveal that sub-harmonic resonance may occur even when the excitation frequency is well above the natural frequency of the linearized system. As the effects of sub-harmonic response cannot be reflected by the averaging formulations, numerical integrations are used to obtain the dynamic responses including sub-harmonic and other frequency components. Furthermore, power flow characteristics of this nonlinear isolation system are examined for a better assessment of the isolation performance. The results show that the occurrences of sub-harmonic resonance may considerably increase both the time-averaged input power and the maximum kinetic energy. Compared with linear systems, the power flows of the nonlinear system might be non-unique and sensitive to the initial conditions. Some suggestions on restricting the maximum deflection and suppressing sub-harmonic resonances are provided for effective designs of nonlinear isolation systems. ► A nonlinear isolation system with a negative stiffness mechanism (NSM) is studied. ► Adding NSM extends greatly the frequency range for effective vibration isolation. ► Effects of amplitude/frequency/initial condition/a on power flow are analysed. ► Isolation performance assessed using power flow is better than transmissibility. ► How to suppress sub-harmonic resonances in NSM isolation system is discussed.